Ireland [videorecording] - The Travel Preview System (Houston, Tex. Travelview International, 1996)
Describes Ireland as a land of venerable kings, copious entertainment and warm hearted people. It is a land distinguished by ancient legends mixed with lovely landscapes.
Title on container :Ireland : the beginning of a great vacation.
VHS.
Keywords: Irish -- Social life and customs; Ireland -- Description and travel